Peelable carrier-attached copper foil with bipolar thin copper layer and preparation method of peelable carrier-attached copper foil

By using a heat-resistant inorganic release layer and a bipolar thin copper layer structure in an ultra-thin peelable carrier copper foil, combined with pulsed electrochemical deposition and ultra-fine roughening treatment, the problems of unstable separation force and high production cost at high temperatures are solved, achieving efficient processing and low-cost production of ultra-fine circuits.

CN121272501APending Publication Date: 2026-01-06JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511363927.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2026-01-06

AI Technical Summary

Technical Problem

Traditional ultra-thin peelable carrier copper foil has unstable separation force at high temperatures, is prone to sticking after repeated pressing, has high production costs, low copper foil utilization, and is difficult to meet the needs of ultra-high density wiring.

Method used

Using a heat-resistant inorganic material as the release layer, a bipolar thin copper layer structure design, combined with pulsed electrochemical deposition and ultrafine roughening treatment, a non-copper functional layer is constructed and coated with a silane coupling agent to improve separation stability and etching performance.

Benefits of technology

It improves the heat resistance and separation stability of the carrier copper foil, reduces production and usage costs, and enables ultra-fine line processing with L/S≤25/25μm, making it compatible with mSAP and ETS processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005609854040000151
    Figure BDA0005609854040000151
  • Figure BDA0005609854040000161
    Figure BDA0005609854040000161
  • Figure HDA0005609854050000011
    Figure HDA0005609854050000011
Patent Text Reader

Abstract

The invention relates to the technical field of manufacturing of electronic materials and electronic components, in particular to a strippable carrier-attached copper foil with a bipolar thin copper layer and a preparation method of the strippable carrier-attached copper foil. The preparation method provided by the invention comprises the following steps: preparing a carrier copper layer; preparing a first inorganic stripping layer on the smooth surface of the carrier copper layer; preparing a first ultra-thin copper layer on the surface of the first inorganic stripping layer; preparing a second inorganic stripping layer on the surface of the first ultra-thin copper layer; preparing a second ultra-thin copper layer on the surface of the second inorganic stripping layer; carrying out hyperfine roughening treatment on the ultrathin copper layer; and constructing a non-copper functional layer on the surface of the roughened ultra-thin copper layer, and carrying out silane coupling agent coating treatment to obtain the strippable carrier-attached copper foil with the bipolar thin copper layer. The inorganic matter with good heat resistance is used as the stripping layer, the heat resistance of the carrier copper foil stripping layer is improved, the two ultra-thin copper layers are sequentially deposited on the surface of the carrier copper layer, the mSAP manufacturing procedure and the ETS manufacturing procedure can be met at the same time, and the production and processing cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials and electronic component manufacturing technology, and in particular to a peelable carrier copper foil with a bipolar thin copper layer and its preparation method. Background Technology

[0002] Thinning and miniaturization are clear development trends in consumer electronics products, exemplified by advanced smartphones. Driven by the demands for smaller device sizes and increased functionality, increasing wiring density to accommodate as many lines as possible in a small area has become a widely accepted solution. Ultra-high density wiring requires compressing line width and spacing as much as possible while meeting performance and reliability requirements. Ultra-thin peelable copper foil is a key material for achieving ultra-fine wiring with line width and spacing L / S ≤ 25 / 25μm.

[0003] The release layer is crucial for ensuring stable separation between the ultra-thin functional copper layer and the carrier layer in ultra-thin peelable carrier copper foil. The composition and uniformity of the release layer directly affect the separability and separation force stability of the ultra-thin peelable carrier copper foil. Traditional carrier copper foils often use organic materials as the release layer, achieving stable and controllable separation between the ultra-thin copper layer and the carrier layer within a certain temperature range. It should be noted that organic materials generally have lower heat resistance than inorganic materials and are prone to decomposition at relatively high temperatures. Based on practical experience, when the lamination temperature exceeds 230℃, carrier copper foils with organic components as the release layer cannot stably maintain separation force. After multiple laminations, the ultra-thin copper layer and the carrier layer may adhere, leading to ineffective separation. Therefore, improving the heat resistance of the carrier copper foil release layer is of great significance for expanding the application areas of carrier copper foil and ensuring its processability after multiple laminations.

[0004] Traditional ultrathin peelable carrier copper foil typically consists of only one ultrathin copper layer with a thickness of no more than 5μm. The ultrathin copper layer is processed into ultra-fine circuits using mSAP or Coreless processes, which results in high production and processing costs and low copper foil utilization. Summary of the Invention

[0005] In view of the shortcomings of the prior art described above, this invention proposes a peelable carrier copper foil with a double-thin copper layer. By selecting an inorganic material with a relatively high heat resistance temperature as the release layer, the heat resistance of the carrier copper foil release layer can be effectively improved, and the usability of the carrier copper foil can be expanded. Two ultra-thin copper layers with a thickness of no more than 5μm are sequentially deposited on the surface of the carrier copper layer, which can simultaneously meet the requirements of mSAP and ETS processes, effectively reducing the production and processing costs of the ultra-thin peelable carrier copper foil and improving the utilization efficiency of the copper foil.

[0006] The first aspect of this invention provides a method for preparing a peelable carrier copper foil with a bipolar thin copper layer, comprising the following steps:

[0007] (1) Preparation of the carrier copper layer;

[0008] (2) A first inorganic release layer was prepared on the smooth surface of the copper layer on the carrier by electrochemical / physical vapor deposition.

[0009] (3) A first extremely thin copper layer was prepared on the surface of the first inorganic stripping layer by pulse electrochemical deposition.

[0010] (4) A second inorganic stripping layer is prepared on the surface of the first ultrathin copper layer by electrochemical deposition or chemical vapor deposition.

[0011] (5) A second extremely thin copper layer was prepared on the surface of the second inorganic stripping layer by pulse electrochemical deposition.

[0012] (6) Perform ultra-fine roughening treatment on the second ultra-thin copper layer;

[0013] (7) A non-copper functional layer is constructed on the surface of the second thin copper layer after roughening treatment, and a silane coupling agent is applied to obtain a peelable carrier copper foil with a bipolar thin copper layer.

[0014] In some embodiments of the present invention, in step (1), the thickness of the carrier copper layer is 12-18 μm, and the surface roughness Rz of the carrier copper layer is between 0.9-1.5 μm.

[0015] In some embodiments of the present invention, in step (1), the method for preparing the carrier copper layer includes: using a titanium roller as the cathode and DSA as the anode in an anode tank, and using acidic copper sulfate containing additives as the electrolyte, a copper foil with uniform thickness and physical properties is deposited on the surface of the titanium cathode roller by direct current electrochemical deposition, thereby obtaining the carrier copper layer.

[0016] In some embodiments of the present invention, in step (2), the first inorganic stripping layer is selected from nickel, nickel-based alloys, cobalt, cobalt-based alloys or molybdenum, and has a thickness of 1-100 nm.

[0017] In some embodiments of the present invention, in steps (3) and (5), the thickness of the first and second ultrathin copper layers is 1-5 μm.

[0018] In some embodiments of the present invention, in steps (3) and (5), the electrolyte used for pulse electrochemical deposition has a copper ion concentration of 90-100 g / L, a sulfuric acid concentration of 125-150 g / L, a chloride ion concentration of 10-15 mg / L, and an additive concentration of 5-15 mg / L.

[0019] In some embodiments of the present invention, in steps (3) and (5), the temperature of the electrolyte used for the pulsed electrochemical deposition is 45-50°C, and the electrode liquid flow rate is 40-45 m³ / h. 3 / h, average current density is 2000-2500A / m 2 The duty cycle is 25%-33%.

[0020] In some embodiments of the present invention, in step (4), the second inorganic exfoliation layer is reduced graphene oxide with a thickness of 1-100 nm.

[0021] In some embodiments of the present invention, in step (4), the concentration of graphene oxide in the electrolyte for electrochemical deposition is 80-120 mg / L, the concentration of sulfuric acid is 80-120 g / L, the temperature of the electrolyte is 28-32°C, and the flow rate of the electrolyte is 2-5 m³ / L. 3 / h, current density is 150-300A / m 2 .

[0022] In some embodiments of the present invention, in step (6), a pulsed current is applied simultaneously during the roughening process.

[0023] In some embodiments of the present invention, in step (6), the concentration of copper ions in the roughening electrolyte is 10-15 g / L, the concentration of sulfuric acid is 90-120 g / L, and the concentration of additives is 10-20 mg / L; the temperature of the electrolyte is 25-30°C, and the flow rate of the electrolyte is 8-12 m³ / L. 3 / h.

[0024] In some embodiments of the present invention, step (7) involves constructing a non-copper functional layer by sequentially preparing a nickel-based barrier layer and a zinc-chromium composite antioxidant layer on the surface of an extremely thin copper layer after roughening treatment using a pulsed electrochemical deposition method.

[0025] In some embodiments of the present invention, in step (7), the silane coupling agent is selected from KBM-503 or KBM-903, the concentration of the silane coupling agent is 0.5wt%-1.5wt%, and the flow rate of the silane coupling agent is 1.0-2.5m. 3 / h, after coating, place in an oven to bake.

[0026] In some embodiments of the present invention, in step (7), a non-copper functional layer is constructed simultaneously on the rough surface of the carrier copper layer and the surface of the ultrathin copper layer, and a silane coupling agent coating treatment is performed.

[0027] The second aspect of the present invention provides a peelable carrier copper foil having a bipolar thin copper layer prepared by the above-described preparation method.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] 1. This invention uses an inorganic material with relatively high heat resistance as the release layer of the carrier copper foil, which can not only improve the usable temperature range of the carrier copper foil, but also improve the stability of the separation force between the ultra-thin copper layer and the carrier copper layer to a certain extent.

[0030] 2. This invention, by introducing a bipolar thin copper layer structural design, increases the functionality of the carrier copper foil, enabling both mSAP and ETS processes to be performed on the same carrier copper foil. The bipolar thin copper layer design helps reduce the production and usage costs of the carrier copper foil.

[0031] 3. This invention achieves controllable deposition of ultra-thin copper layers with ultrafine grains through additive-assisted pulsed electrochemical deposition, which is beneficial to improving the rapid etching performance of ultra-thin copper layers and the line width and line spacing of substrate circuits.

[0032] 4. This invention reduces the surface roughness of the ultra-thin copper layer while ensuring the peel strength between the ultra-thin copper layer and the substrate material through an ultra-fine roughening surface treatment process. It also helps to improve the etching performance of the ultra-thin copper layer and achieve ultra-fine lines with L / S not exceeding 25 / 25μm.

[0033] 5. The non-copper functional layer constructed by pulse electrochemical deposition in this invention has a small film thickness and high film density, which can ensure the chemical resistance and heat resistance of copper foil at a low content. On the basis of pulse electrochemical deposition of non-copper functional layer, a chemical bonding layer is constructed, which can increase the density of active sites per unit area, improve the quality of chemical bonding layer, and improve the peel strength between ultra-thin copper layer and carrier material. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the preparation process of a peelable carrier copper foil with a bipolar thin copper layer according to an embodiment of the present invention.

[0035] Figure 2 This is a schematic diagram of a peelable carrier copper foil with a bipolar thin copper layer according to an embodiment of the present invention.

[0036] Figure 3 This is a schematic diagram of the processing and separation process of a peelable carrier copper foil with a bipolar thin copper layer according to an embodiment of the present invention.

[0037] Figure label:

[0038] S01 - Carrier copper layer; S02 - First inorganic release layer; S03 - First ultra-thin copper layer; S04 - Second inorganic release layer; S05 - Second ultra-thin copper layer; S06 - Non-copper functional layer and silane coupling agent layer. Detailed Implementation

[0039] The following description, in conjunction with the accompanying drawings and specific embodiments, further illustrates the present invention of a peelable carrier copper foil with a bipolar thin copper layer and its preparation method.

[0040] The first aspect of this invention provides a method for preparing a peelable carrier copper foil having a bipolar thin copper layer, such as... Figure 1 As shown, it includes the following steps:

[0041] (1) Preparation of the carrier copper layer;

[0042] (2) A first inorganic release layer was prepared on the smooth surface of the copper layer on the carrier by electrochemical / physical vapor deposition.

[0043] (3) A first extremely thin copper layer was prepared on the surface of the first inorganic stripping layer by pulse electrochemical deposition.

[0044] (4) A second inorganic stripping layer is prepared on the surface of the first ultrathin copper layer by electrochemical deposition or chemical vapor deposition.

[0045] (5) A second extremely thin copper layer was prepared on the surface of the second inorganic stripping layer by pulse electrochemical deposition.

[0046] (6) Perform ultra-fine roughening treatment on the second ultra-thin copper layer;

[0047] (7) A non-copper functional layer is constructed on the surface of the second thin copper layer after roughening treatment, and a silane coupling agent is applied to obtain a peelable carrier copper foil with a bipolar thin copper layer.

[0048] In some embodiments of the present invention, in step (1), the thickness of the carrier copper layer is 12-18 μm, the smooth surface roughness Rz of the carrier copper layer is between 0.9-1.5 μm, and the rough surface roughness is between 1 and 2 μm. In some specific embodiments of the present invention, the thickness of the carrier copper layer is 18 μm.

[0049] In some embodiments of the present invention, step (1) of preparing the carrier copper layer includes: using a titanium roller as the cathode and a DSA as the anode in an anode tank, and using acidic copper sulfate containing additives as the electrolyte, a copper foil of uniform thickness and physical properties is deposited on the surface of the titanium cathode roller by direct current electrochemical deposition, thereby obtaining the carrier copper layer. In some specific embodiments of the present invention, the additive is hydroxyethyl cellulose or collagen. The smooth surface roughness of the carrier layer copper foil is controlled by offline polishing and online polishing, and the crystal structure and roughness of the surface roughness of the carrier layer copper foil are controlled by additives and current density.

[0050] In some embodiments of the present invention, in step (1), the concentration of copper ions in the electrolyte is 80-90 g / L, the concentration of sulfuric acid is 120-150 g / L, the concentration of chloride ions is 15-25 mg / L, and the concentration of the additive is 15-30 mg / L. Preferably, the additive is selected from hydroxyethyl cellulose or collagen; more preferably, the weight-average molecular weight of the collagen is 300-500 kDa. When the additive is selected from hydroxyethyl cellulose, the additive concentration in the electrolyte is preferably 20-30 mg / L; when the additive is selected from collagen, the additive concentration in the electrolyte is preferably 15-25 mg / L.

[0051] In some embodiments of the present invention, in step (1), the temperature of the electrolyte is 45-50°C, which can be 45-46°C, 46-47°C, 47-48°C, 48-49°C, or 49-50°C, and the flow rate of the electrolyte is 40-45 m³ / h. 3 / h can be 40-41m 3 / h, 41-42m 3 / h, 42-43m 3 / h, 43-44m 3 / h, or 44-45m 3 / h, current density is 7500-8500 A / m 2 It can provide 7500-7700A / m 2 7700-7900A / m 2 7900-8000A / m 2 8000-8200A / m 2 8200-8400A / m 2 It can also be 8400-8500A / m 2 .

[0052] In some embodiments of the present invention, in step (2), the first inorganic release layer is selected from nickel, nickel-based alloys, cobalt, cobalt-based alloys, or molybdenum, and has a thickness of 1-100 nm, which can be 1-10 nm, 10-20 nm, 20-30 nm, 30-40 nm, 40-50 nm, 50-60 nm, 60-70 nm, 70-80 nm, 80-90 nm, or 90-100 nm, preferably 8-12 nm. In some preferred embodiments of the present invention, the first inorganic release layer is nickel, and the thickness and quality of the metallic nickel layer can be precisely controlled by controlling the process parameters of electrochemical deposition and PVD deposition. When the first inorganic release layer is prepared using an electrochemical deposition method, the concentration of nickel ions in the electrolyte used for electrochemical deposition is 5-10 g / L, the concentration of potassium pyrophosphate is 150-200 g / L, the pH of the electrolyte is 10.0-10.5, the temperature of the electrolyte is 38-42℃ (it can be 38-40℃ or 40-42℃), and the flow rate of the electrolyte is 5-10 m³ / h. 3 / h can be 5-7m 3 / h, 7-9m 3 / h, or 9-10m 3 / h, current density is 200-300A / m 2 It can provide 200-250A / m 2 250-300A / m 2 It can also be 300-350A / m 2 When the first inorganic release layer is prepared by physical vapor deposition, the physical vapor deposition is DC sputtering deposition, the target material is a nickel target, the vacuum degree is 100-110 mTorr (or 100-105 mTorr, or 105-110 mTorr), the argon flow rate is 80-150 sccm (or 80-90 sccm, 90-100 sccm, 100-110 sccm, 110-120 sccm, 120-130 sccm, 130-140 sccm, or 140-150 sccm), the sputtering power is 10-20 kW (or 10-15 kW, or 15-20 kW), and the sputtering time is 5-15 min (or 5-10 min, or 10-15 min).

[0053] In some embodiments of the present invention, in steps (3) and (5), the concentration of copper ions in the electrolyte used for pulsed electrochemical deposition is 90-100 g / L, the concentration of sulfuric acid is 125-150 g / L, the concentration of chloride ions is 10-15 mg / L, and the concentration of additives is 5-15 mg / L. In some specific embodiments of the present invention, the additives are selected from sodium 2-mercapto-5-benzimidazole sulfonate or sodium tungstate. When the additive is selected from sodium 2-mercapto-5-benzimidazole sulfonate, the concentration of the additive in the electrolyte is 5-10 mg / L; when the additive is selected from sodium tungstate, the concentration of the additive in the electrolyte is 10-15 mg / L. Controllable deposition of ultra-fine grained, ultra-thin copper layers is achieved through additive-assisted pulsed electrochemical deposition. Pulsed electrochemical deposition can effectively increase the peak current density and overpotential during the electrochemical deposition process, which is beneficial for achieving ultra-fine crystal nucleation and growth. Additives regulate the overpotential during the electrochemical reduction of copper ions by forming complexes with them, thereby controlling the crystal structure of the copper foil. Furthermore, additives can be doped between grain boundaries in the copper foil crystal structure, suppressing recrystallization of adjacent grains during heat treatment and use. Therefore, additive-assisted pulsed electrochemical deposition can achieve ultra-fine crystal structure copper foils with excellent crystal stability.

[0054] In some embodiments of the present invention, in steps (3) and (5), the temperature of the electrolyte is 45-50°C, or it can be 45-47°C, 47-49°C, or 49-50°C, and the electrode liquid flow rate is 40-45 m³ / h. 3 / h, which can be 40-42m 3 / h, 42-44m 3 / h, or 44-45m 3 / h, average current density is 2000-2500A / m 2 It can provide 2000-2200A / m 2 2200-2400A / m 2 It can also be 2400-2500A / m 2 The duty cycle is 25%-33%, but it can be 20%-25%, 25%-30%, or 30%-33%.

[0055] In some embodiments of the present invention, in step (4), the second inorganic exfoliation layer is reduced graphene oxide with a thickness of 1-100 nm, which can be 1-10 nm, 10-20 nm, 20-30 nm, 30-40 nm, 40-50 nm, 50-60 nm, 60-70 nm, 70-80 nm, 80-90 nm, or 90-100 nm, preferably 8-12 nm. The concentration of graphene oxide in the electrolyte for electrochemical deposition is 80-200 mg / L, which can be 80-100 mg / L, 100-120 mg / L, 120-140 mg / L, 140-160 mg / L, 160-180 mg / L, or 180-200 mg / L. The concentration of sulfuric acid is 80-120 g / L, which can be 80-100 g / L or 100-120 g / L. The temperature of the electrolyte is 28-32℃, which can be 28-30℃ or 30-32℃. The flow rate of the electrolyte is 2-5 m³ / h. 3 / h, which can be 2-3m 3 / h, 3-4m 3 / h, or 4-5m 3 / h, current density is 150-300A / m 2 It can provide 150-200A / m 2 200-250A / m 2 It can also be 250-300A / m 2 In other embodiments of the present invention, a reduced graphene oxide layer is prepared using chemical vapor deposition. The reduced graphene oxide serves as the second inorganic exfoliation layer; its high conductivity promotes the uniform electrochemical deposition of the ultrathin copper layer. Simultaneously, the layered structure of the reduced graphene oxide binds to the first ultrathin copper layer through weak van der Waals forces, providing controllable interfacial slip behavior during the exfoliation process and enhancing its stability.

[0056] In some embodiments of the present invention, in step (6), a pulsed current is simultaneously applied during the roughening process. The average current density of the pulsed current is 500-800 A / m. 2 It can provide 500-600A / m 2 600-700A / m 2 700-750A / m 2 It can also be 750-800A / m 2 The duty cycle is 15%-30%, which can be 15%-20%, 20%-25%, or 25%-30%. The processing time is 8-12 seconds, which can be 8-10 seconds or 10-12 seconds. The number of processing times is 2-3.

[0057] In some embodiments of the present invention, in step (6), the concentration of copper ions in the roughening electrolyte is 10-15 g / L, the concentration of sulfuric acid is 90-120 g / L, and the concentration of additives is 10-20 mg / L; the temperature of the electrolyte is 25-30°C, which can be 25-27°C, 27-29°C, or 29-30°C, and the electrolyte flow rate is 8-12 m³ / h. 3 / h, which can be 8-10m 3 / h, or 10-12m 3 / h. In some specific embodiments of the present invention, the additive is sodium tungstate. An additive-assisted pulsed electrochemical deposition process is used to perform ultra-fine roughening treatment on the ultra-thin copper layer, enhancing the bonding stability between the ultra-thin copper layer and the substrate material. Ultra-fine roughening treatment can achieve copper nodules with an average size in the sub-micron range, reducing the surface profile of the copper foil while increasing the effective bonding area between the copper foil and the substrate material, thereby achieving a stable bond between the ultra-thin copper layer and the substrate material.

[0058] In some embodiments of the present invention, step (7) involves constructing a non-copper functional layer by sequentially preparing a nickel-based barrier layer (0.1-10 nm thick) and a zinc-chromium composite antioxidant layer (0.2-20 nm thick) on the surface of an extremely thin copper layer after roughening treatment using a pulsed electrochemical deposition method. In some embodiments of the present invention, the concentration of nickel ions in the electrolyte used for preparing the nickel-based barrier layer by pulsed electrochemical deposition is 10-20 g / L, the concentration of boric acid is 30-50 g / L, and the concentration of sodium hypophosphite is 50-60 g / L; the temperature of the electrolyte used for pulsed electrochemical deposition is 35-40°C, which can be 35-37°C, 37-39°C, or 39-40°C, and the electrolyte flow rate is 5-10 m³ / h. 3 / h, which can be 5-7m 3 / h, 7-9m 3 / h, or 9-10m 3 / h, average current density is 25-50A / m 2 It can provide 25-30A / m 2 30-35A / m 2 35-40A / m 2 40-45A / m 2 It can also be 45-50A / m 2The duty cycle is 20%-33%, which can be 20%-25%, 25%-30%, or 30%-33%. The processing time is 8-12 seconds, which can be 8-10 seconds or 10-12 seconds. The electrolyte used for pulsed electrochemical deposition to prepare a zinc-based high-temperature antioxidant layer has a zinc ion concentration of 5-10 g / L, a boric acid concentration of 30-50 g / L, and a sodium hypophosphite concentration of 50-60 g / L. The electrolyte temperature is 35-40℃, which can be 35-37℃, 37-39℃, or 39-40℃. The electrolyte flow rate is 5-10 m³ / h. 3 / h, which can be 5-7m 3 / h, 7-9m 3 / h, or 9-10m 3 / h, average current density is 25-50A / m 2 It can provide 25-30A / m 2 30-35A / m 2 35-40A / m 2 40-45A / m 2 It can also be 45-50A / m 2 The duty cycle is 20%-33%, which can be 20%-25%, 25%-30%, or 30%-33%; the processing time is 8-12s, which can be 8-10s or 10-12s; the concentration of hexavalent chromium ions (chromic anhydride) in the electrolyte used for pulse electrochemical deposition to prepare chromium-based room-temperature antioxidant layers is 2-5 g / L; the electrolyte temperature is 35-40℃, which can be 35-37℃, 37-39℃, or 39-40℃; and the electrolyte flow rate is 5-10 m³ / min. 3 / h, which can be 5-7m 3 / h, 7-9m 3 / h, or 9-10m 3 / h, average current density is 25-50A / m 2 It can provide 25-30A / m 2 30-35A / m 2 35-40A / m 2 40-45A / m 2 It can also be 45-50A / m 2 The duty cycle is 20%-33%, which can be 20%-25%, 25%-30%, or 30%-33%, and the processing time is 8-12s, which can be 8-10s or 10-12s. The nanoscale thickness of the non-copper functional layer is mainly used to improve the chemical resistance and high temperature resistance of copper foil.

[0059] The silane coupling agent chemical bonding layer enhances the peel strength of the interfacial bond by forming chemical bonds between the copper foil and the carrier material. In some embodiments of the present invention, in step (7), the silane coupling agent is selected from KBM-503 or KBM-903, the concentration of the silane coupling agent is 0.5wt%-1.5wt%, which can be 0.5wt%-1.0wt% or 1.0wt%-1.5wt%, and the flow rate of the silane coupling agent is 1.0-2.5m. 3 / h can be 1.0-1.5m 3 / h, 1.5-2.0m 3 / h, or 2.0-2.5m 3 The coating is applied per hour and then baked in an oven. Preferably, the baking temperature is 110-180℃, but can be 110-120℃, 120-130℃, 130-140℃, 140-150℃, 150-160℃, 160-170℃, or 170-180℃.

[0060] In some embodiments of the present invention, in step (7), a non-copper functional layer is constructed simultaneously on the rough surface of the carrier copper layer and the surface of the ultrathin copper layer, and a silane coupling agent coating treatment is performed.

[0061] A second aspect of the present invention provides a peelable carrier copper foil having a bipolar thin copper layer, prepared using the above-described preparation method. For example... Figure 2 As shown, the peelable copper foil with a bipolar thin copper layer includes a carrier copper layer S01. A first inorganic release layer S02, a first ultrathin copper layer S03, a second inorganic release layer S04, a second ultrathin copper layer S05, a non-copper functional layer, and a silane coupling agent layer S06 are sequentially stacked on the smooth surface of the carrier copper layer. In some embodiments of the present invention, a non-copper functional layer and a silane coupling agent layer S06 are also disposed on the rough surface of the carrier copper layer to ensure that the carrier copper layer does not oxidize during processing. The peelable copper foil with a bipolar thin copper layer provided by the present invention has good separation and etching performance.

[0062] The present invention provides a process flow for processing and separating peelable carrier copper foil with a bipolar thin copper layer, which is referred to as follows: Figure 3 It includes the following steps:

[0063] S1. First pressing: The peelable carrier copper foil with a bipolar thin copper layer is hot-pressed onto the resin substrate (substrate 1) so that the outermost non-copper functional layer and the silane coupling agent layer S06 are cured and bonded to the substrate 1.

[0064] S2. First separation: Peel off at the interface of the second inorganic release layer S04 to separate the entire structure of the carrier copper layer S01 / first inorganic release layer S02 / first ultrathin copper layer S03 from the substrate (the carrier copper layer S01 provides support for this structure), exposing the surface of the second ultrathin copper layer S05. At this time, the second ultrathin copper layer S05, the non-copper functional layer and the silane coupling agent layer S06 remain on the substrate 1.

[0065] S3. Remove the second release layer: Using the carrier copper layer S01 as a support substrate, the second inorganic release layer S04 is completely removed by chemical cleaning or plasma cleaning, exposing the clean surface of the first ultrathin copper layer S03.

[0066] S4. Fine circuit processing: Photolithography, etching or laser direct writing are performed on the exposed first ultra-thin copper layer S03 to form fine circuits;

[0067] S5. Secondary lamination: Lamination of another resin substrate (substrate 2) onto the current structure and curing it to cover and protect the fine circuitry (first ultrathin copper layer S03) that has been completed below.

[0068] S6. Second separation: Peel off at the interface of the first inorganic release layer S02, remove the carrier copper layer S01 and the first inorganic glass layer S02, and obtain a substrate product with fine lines (formed by the first ultrathin copper layer S03) with the substrate 2 as the permanent support.

[0069] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention.

[0070] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, this invention can be implemented using any prior art methods, apparatus, and materials similar to or equivalent to those described in the embodiments of this invention, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention.

[0071] Unless otherwise stated, the experimental methods, detection methods, and preparation methods disclosed in this invention all employ conventional techniques in analytical chemistry and related fields. Unless otherwise stated, all materials and equipment used in this invention are commercially available.

[0072] Example 1

[0073] The method for preparing a peelable carrier copper foil with a bipolar thin copper layer in this embodiment includes the following steps:

[0074] (1) Preparation of the carrier copper layer: In an anode tank, using a titanium roller as the cathode and DSA as the anode, and acidic copper sulfate containing additives as the electrolyte, a copper foil with a uniform thickness of 18 μm is deposited on the surface of the titanium cathode roller by direct current electrochemical deposition, which is the carrier copper layer. The key process parameters in the production of the carrier copper layer are as follows:

[0075] Copper ion concentration: 90 g / L

[0076] Sulfuric acid concentration: 120 g / L

[0077] Chloride ion concentration: 15 mg / L

[0078] Hydroxyethyl cellulose concentration: 20 mg / L

[0079] Electrolyte temperature: 50℃

[0080] Electrolyte flow rate: 45m³ 3 / h

[0081] Current density: 8500A / m 2 .

[0082] (2) Preparation of the first inorganic release layer: A 10 nm thick layer of metallic nickel was deposited on the smooth surface of the copper substrate using electrochemical deposition as the first inorganic release layer. The key process parameters for the electrochemical deposition of metallic nickel are as follows:

[0083] Nickel ion concentration: 5 g / L

[0084] Potassium pyrophosphate concentration: 150 g / L

[0085] pH: 10.0

[0086] Electrolyte temperature: 40℃

[0087] Electrolyte flow rate: 5m 3 / h

[0088] Current density: 200A / m 2 .

[0089] (3) Preparation of the first ultrathin copper layer: A first ultrathin copper layer with a thickness of 3 μm was deposited on the surface of the first release layer by pulsed electrochemical deposition assisted by additives. Pulsed electrodeposition can increase the nucleation density and effectively reduce the grain size. The introduction of additives regulates the electrochemical reduction overpotential of Cu-complexes, thereby regulating the electrochemical deposition of copper atoms. The key process parameters in the deposition of the first ultrathin copper layer are as follows:

[0090] Copper ion concentration: 90 g / L

[0091] Sulfuric acid concentration: 125g / L

[0092] Chloride ion concentration: 10 mg / L

[0093] 2-Mercapto-5-benzimidazole sulfonate sodium concentration: 10 mg / L

[0094] Electrolyte temperature: 45℃

[0095] Electrolyte flow rate: 45m³ 3 / h

[0096] Average current density: 2000 A / m 2

[0097] Duty cycle: 25%.

[0098] (4) Preparation of the second inorganic exfoliation layer: A 1.0 nm thick layer of reduced graphene oxide (rGO) was deposited on the surface of the first ultrathin copper layer via electrochemical deposition as the second inorganic exfoliation layer. Reduced graphene oxide (rGO) exhibits excellent electrical conductivity, thermal conductivity, and exfoliability. The key process parameters for the electrochemical deposition of reduced graphene oxide on the surface of the first ultrathin copper layer are as follows:

[0099] GO concentration: 100 mg / L

[0100] H2SO4 concentration: 100g / L

[0101] Electrolyte temperature: 30℃

[0102] Electrolyte flow rate: 2.5m 3 / h

[0103] Current density: 200A / m 2 .

[0104] (5) Preparation of the second ultrathin copper layer: A second ultrathin copper layer with a thickness of 3 μm is deposited on the surface of the second inorganic stripping layer by pulsed electrochemical deposition assisted by additives. Pulsed electrodeposition can increase the nucleation density and effectively reduce the grain size. The introduction of additives regulates the electrochemical reduction overpotential of Cu-complexes, thereby regulating the electrochemical deposition of copper atoms. The process parameters in the deposition of the second ultrathin copper layer are the same as those in step (3) for preparing the first ultrathin copper layer.

[0105] (6) Ultra-thin copper layer ultra-fine roughening treatment: During the roughening surface treatment process, pulsed current and additives with grain-refining effects are introduced to achieve sub-micron diameter ultra-fine copper nodules. These ultra-fine copper nodules not only reduce the surface roughness after the ultra-thin copper layer roughening treatment but also help shorten the etching time in downstream circuit processing, reducing the risk of micro-short circuits caused by incomplete etching. The key process parameters in the second ultra-thin copper layer ultra-fine roughening treatment process are as follows:

[0106] Copper ion concentration: 10 g / L

[0107] Sulfuric acid concentration: 120 g / L

[0108] Sodium tungstate concentration: 20 mg / L

[0109] Electrolyte temperature: 30℃

[0110] Electrolyte flow rate: 10m 3 / h

[0111] Average current density: 750 A / m 2

[0112] Duty cycle: 30%

[0113] Processing time: 10s

[0114] Number of processing attempts: 3.

[0115] (7) Construction of non-copper functional layers: A nickel-containing barrier layer, a zinc-containing high-temperature anti-oxidation layer, and a chromium-containing room-temperature anti-oxidation layer are constructed on the surface of the second ultrathin copper layer and the rough surface of the carrier copper layer by pulsed electrochemical deposition. The key process parameters for constructing the non-copper metal functional layers are as follows:

[0116] Nickel-based barrier layer electrolyte: nickel ion concentration 10 g / L; boric acid concentration 50 g / L; sodium hypophosphite concentration 60 g / L;

[0117] Zinc-based high-temperature antioxidant electrolyte: zinc ion concentration 10g / L, boric acid concentration 50g / L, sodium hypophosphite concentration 60g / L;

[0118] Chromium-based room temperature antioxidant electrolyte: hexavalent chromium ion (chromium anhydride) concentration 2 g / L, pH 11;

[0119] Electrolyte temperature: 40℃

[0120] Electrolyte flow rate: 5m 3 / h

[0121] Average current density: 50A / m 2

[0122] Duty cycle: 33%

[0123] Processing time: 10s.

[0124] (8) Coating with silane coupling agent: A silane coupling agent is simultaneously coated on the surface of the second ultrathin copper layer with the non-copper functional layer and the rough surface of the carrier copper layer. The silane coupling agent forms O-Si-O chemical bonds with the hydroxyl groups suspended on the copper foil surface, improving the peel strength between the ultrathin copper layer and the carrier material. The key process parameters for coating with the silane coupling agent are as follows:

[0125] Silane coupling agent: KBM-503

[0126] Silane coupling agent concentration: 1.0 wt%

[0127] Silane coupling agent flow rate 2m 3 / h

[0128] Oven temperature: 120℃.

[0129] Example 2

[0130] The difference between this embodiment and Example 1 is that the type and concentration of additives in the production process of the copper carrier layer in step (1) were adjusted. The concentration of hydroxyethyl cellulose, which was 20-30 mg / L, was changed to 15-25 mg / L of collagen (300-500 kDa), while other parameters remained unchanged.

[0131] Example 3

[0132] The difference between this embodiment and Embodiment 1 lies in the adjustment of the production method of the first inorganic lift-off layer in step (2). Physical vapor deposition is used instead of electrochemical deposition on the copper substrate to deposit a nanometer-thick layer of metallic nickel as the first inorganic lift-off layer. The key process parameters for physical vapor deposition of the nanometer-thick metallic nickel layer are as follows:

[0133] Target material: Nickel target (purity: 99.999 at%)

[0134] Vacuum degree: 100mTorr

[0135] Argon flow rate: 100 sccm

[0136] Sputtering power: 15kW

[0137] Sputtering time: 10 min.

[0138] Example 4

[0139] The difference between this embodiment and Embodiment 1 lies in the adjustment of the process parameters in step (3) during the pulsed electrochemical deposition process to prepare the first extremely thin copper layer. The average current density was reduced from 2000 A / m 2 Adjusted to 2500A / m 2 The duty cycle was adjusted from 25% to 33%, while other parameters remained unchanged. The key process parameters for the first ultrathin copper layer deposition process are as follows:

[0140] Copper ion concentration: 90 g / L

[0141] Sulfuric acid concentration: 125g / L

[0142] Chloride ion concentration: 10 mg / L

[0143] 2-Mercapto-5-benzimidazole sulfonate sodium concentration: 10 mg / L

[0144] Electrolyte temperature: 45℃

[0145] Electrolyte flow rate: 45m³ 3 / h

[0146] Average current density: 2500 A / m 2

[0147] Duty cycle: 33%.

[0148] Example 5

[0149] The difference between this embodiment and Embodiment 1 is that the process parameters of the second inorganic exfoliation layer in step (4) have been adjusted. The GO concentration has been adjusted from 100 mg / L to 200 mg / L, and the current density has been adjusted from 200 A / m² to 200 mg / L. 2 Adjusted to 250A / m 2 All other parameters remain unchanged. The key process parameters for the electrochemical deposition and reduction of graphene oxide on the surface of the first ultrathin copper layer are as follows:

[0150] GO concentration: 200 mg / L

[0151] H2SO4 concentration: 100g / L

[0152] Electrolyte temperature: 30℃

[0153] Electrolyte flow rate: 2.5m 3 / h

[0154] Current density: 250A / m 2 .

[0155] Example 6

[0156] The difference between this embodiment and Embodiment 1 is that the production process parameters of the second ultrathin copper layer in step (5) are adjusted. The additive in the electrochemical deposition process of the second ultrathin copper layer is changed from sodium 2-mercapto-5-benzimidazole sulfonate with a concentration of 5-10 mg / L to sodium tungstate with a concentration of 10-15 mg / L, while the other parameters remain unchanged.

[0157] Example 7

[0158] The difference between this embodiment and Embodiment 1 is that the process parameters for electrochemical deposition in steps (6) and (7) are adjusted. The pulsed electrochemical deposition operation in steps (6) and (7) is changed to direct current electrochemical deposition, while the other parameters remain unchanged.

[0159] Comparative Example 1

[0160] The difference between this comparative example and Example 1 is that after constructing the first inorganic release layer and the first ultrathin copper layer on the smooth surface of the carrier copper layer, ultra-fine roughening treatment, construction of a non-copper functional layer, and coating with a silane coupling agent (i.e., surface treatment) are performed directly. The final product obtained in this comparative example is a carrier copper foil adapted to the mSAP process.

[0161] Comparative Example 2

[0162] The difference between this comparative example and Example 1 is that a first inorganic release layer and a first ultrathin copper layer are constructed on the smooth surface of the carrier copper layer, and then the rough surface of the carrier copper layer is roughened. Meanwhile, a non-copper functional layer is directly constructed on the surface of the first ultrathin copper layer (the first ultrathin copper layer is not subjected to ultra-fine roughening treatment or silane coupling agent coating). The final product obtained in this comparative example is a carrier copper foil adapted to the ETS process.

[0163] Comparative Example 3

[0164] The difference between this comparative example and Example 1 is that after constructing the first inorganic release layer and the first ultrathin copper layer on the smooth surface of the carrier copper layer, surface treatment is simultaneously performed on both the rough surface of the carrier copper layer and the rough surface of the first ultrathin copper layer. The surface treatment includes ultra-fine roughening, construction of a non-copper functional layer, and coating with a silane coupling agent. The final product obtained in this comparative example is a carrier copper foil adapted for Coreless processes.

[0165] The separation and etching performance of the products from the above embodiments and comparative examples were tested, and the results are shown in Table 1 below:

[0166] Table 1 Comparison of separation and etching performance of the examples and comparative samples

[0167]

[0168]

[0169] As shown in Table 1, the average separation force of Examples 1-7 of the present invention is stable at 9.61-10.83 gf / cm, indicating moderate and controllable adhesion to the substrate, good etching precision, and compatibility with advanced mSAP+ETS processes, meeting the requirements of high-density interconnect (HDI) boards. In contrast, Comparative Examples 1-3 are only compatible with a single process.

[0170] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A method for producing a peelable carrier copper foil with a bipolar thin copper layer, characterized by, It comprises the following steps: (1) preparing a carrier copper layer; (2) preparing a first inorganic stripping layer on the smooth surface of the carrier copper layer by an electrochemical / physical vapor deposition method; (3) preparing a first ultra-thin copper layer on the surface of the first inorganic stripping layer by a pulse electrochemical deposition method; (4) preparing a second inorganic stripping layer on the surface of the first ultra-thin copper layer by an electrochemical deposition or chemical vapor deposition method; (5) preparing a second ultra-thin copper layer on the surface of the second inorganic stripping layer by a pulse electrochemical deposition method; (6) performing an ultra-fine roughening treatment on the second ultra-thin copper layer; (7) constructing a non-copper functional layer on the surface of the second ultra-thin copper layer after the roughening treatment and performing silane coupling agent coating treatment to obtain a strippable carrier copper foil with double ultra-thin copper layers.

2. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 1, characterized in that, In step (1), one or more of the following features are included: (a) the thickness of the carrier copper layer is 12-18 μm, and the smoothness roughness Rz of the carrier copper layer is between 0.9-1.5 μm; (b) the method for preparing the carrier copper layer comprises: in an anode tank, using a titanium roller as a cathode, a DSA as an anode, and an acidic copper sulfate containing an additive as an electrolyte, depositing a copper foil with uniform thickness and properties on the surface of the titanium cathode roller by direct current electrochemical deposition, thereby obtaining the carrier copper layer.

3. The process for producing a peelable carrier copper foil with a bipolar thin copper layer according to claim 2, wherein In step (1), one or more of the following features are included: (b1) the thickness of the carrier copper layer is 18 μm; (b2) the additive is selected from hydroxyethyl cellulose or collagen; (b3) the concentration of copper ions in the electrolyte is 80-90 g / L, the concentration of sulfuric acid is 120-150 g / L, the concentration of chloride ions is 15-25 mg / L, and the concentration of the additive is 15-30 mg / L; (b4) the temperature of the electrolyte is 45-50°C, the flow rate of the electrolyte is 40-45 m 3 / h, and the current density is 7500-8500 A / m 2 .

4. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 1, characterized in that, One or more of the following features are included: (a) in step (2), the first inorganic stripping layer is selected from nickel, nickel-based alloy, cobalt, cobalt-based alloy, or molybdenum, and the thickness is 1-100 nm; (b) in steps (3) and (5), the thickness of the first ultra-thin copper layer and the second ultra-thin copper layer is 1-5 μm; (c) in steps (3) and (5), the concentration of copper ions in the electrolyte used for pulse electrochemical deposition is 90-100 g / L, the concentration of sulfuric acid is 125-150 g / L, the concentration of chloride ions is 10-15 mg / L, and the concentration of the additive is 5-15 mg / L; (d) In step (3) and step (5), the temperature of the electrolyte is 45-50℃, the flow rate of the electrolyte is 40-45m 3 / h, and the average current density is 2000-2500A / m 2 , and the duty cycle is 25%-33%. (e) in step (4), the second inorganic stripping layer is reduced graphene oxide, and the thickness is 1-100 nm.

5. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 4, characterized in that, One or more of the following features are included: (a1) in step (2), the first inorganic stripping layer is nickel; the concentration of nickel ions in the electrolyte used for electrochemical deposition is 5-10 g / L, the concentration of potassium pyrophosphate is 150-200 g / L, the pH of the electrolyte is 10.0-10.5, the temperature of the electrolyte is 38-42℃, the flow rate of the electrolyte is 5-10 m 3 / h, and the current density is 200-300 A / m 2 ; (a2) in step (2), the physical vapor deposition is direct current sputtering deposition, the target material is a nickel target, the vacuum degree is 100-110 mTorr, the argon flow rate is 80-150 sccm, the sputtering power is 10-20 kW, and the sputtering time is 5-15 min; (c1) the additive is 2-mercapto-5-benzimidazole sodium sulfonate or sodium tungstate; (e1) in step (4), the concentration of graphene oxide in the electrolyte for electrochemical deposition is 80-200 mg / L, the concentration of sulfuric acid is 80-120 g / L, the temperature of the electrolyte is 28-32 ℃, the flow rate of the electrolyte is 2-5 m 3 / h, and the current density is 150-300 A / m 2 .

6. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 1, characterized in that, One or more of the following features are included: (a) in step (6), a pulse current is applied simultaneously during the ultra-fine roughening treatment process; (b) In step (6), the concentration of copper ions in the electrolyte for the super-fine roughening treatment is 10-15 g / L, the concentration of sulfuric acid is 90-120 g / L, and the concentration of the additive is 10-20 mg / L; the temperature of the electrolyte is 25-30 °C, and the flow rate of the electrolyte is 8-12 m 3 / h. (b) In step (6), the concentration of copper ions in the electrolyte for the super-fine roughening treatment is 10-15 g / L, the concentration of sulfuric acid is 90-120 g / L, and the concentration of the additive is 10-20 mg / L; the temperature of the electrolyte is 25-30 °C, and the flow rate of the 7. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 6, characterized in that, One or more of the following features are included: (a1) the average current density of the pulsed current is 500-800 A / m 2 , the duty cycle is 15%-30%, the processing time is 8-12 s, and the processing times is 2-3 times; (b1) the additive is sodium tungstate.

8. The process for preparing a peelable carrier-copper foil with a bipolar thin copper layer according to claim 1, wherein One or more of the following features are included: (a) in step (7), the constructing non-copper functional layer comprises preparing nickel-based barrier layer and zinc-chromium composite anti-oxidation layer on the surface of the roughened ultra-thin copper layer by pulse electrochemical deposition method; (b) in step (7), the silane coupling agent is selected from KBM-503 or KBM-903, the concentration of the silane coupling agent is 0.5 wt% - 1.5 wt%, the flow rate of the silane coupling agent is 1.0 - 2.5 m 3 / h, and is placed in an oven for baking after coating; (c) in step (7), the rough surface of the carrier copper layer is synchronously constructed with the non-copper functional layer on the surface of the ultra-thin copper layer, and then is coated with silane coupling agent.

9. The method for preparing a peelable carrier copper foil with a bipolar thin copper layer as described in claim 8, characterized in that, The method comprises one or more of the following features: (a1) the concentration of nickel ions in the electrolyte used for preparing the nickel-based barrier layer by pulse electrochemical deposition is 10-20 g / L, the concentration of boric acid is 30-50 g / L, and the concentration of sodium hypophosphite is 40-60 g / L; the zinc-chromium composite anti-oxidation layer comprises zinc-based high-temperature anti-oxidation layer and chromium-based normal-temperature anti-oxidation layer; the pulse electrochemical deposition for preparing the zinc-chromium composite anti-oxidation layer comprises preparing the zinc-based high-temperature anti-oxidation layer on the surface of the nickel-based barrier layer, and then preparing the chromium-based normal-temperature anti-oxidation layer on the surface of the zinc-based high-temperature anti-oxidation layer; (a2) the temperature of the electrolyte used for the pulse electrochemical deposition to prepare the nickel-based barrier layer is 35-40℃, the electrolyte flow rate is 5-10 m 3 / h, the average current density is 25-50 A / m 2 , the duty cycle is 20%-33%, and the treatment time is 8-12 s; (b1) the temperature of the baking is 110-180℃.

10. The peelable carrier copper foil with bipolar ultra-thin copper layer prepared by the method according to any one of claims 1-9.